Characterization of Foxp3+CD4+CD25+ and IL-10-secreting CD4+CD25+ T cells during cure of colitis. - Uhlig, H; Coombes, J; Mottet, C; Izcue, A; Thompson, C; Fanger, A; Tannapfel, A; Fontenot, J; Ramsdell, F; Powrie, F (2006)
CD4+CD25+ regulatory T cells can prevent and resolve intestinal inflammation in the murine T cell transfer model of colitis. Using Foxp3 as a marker of regulatory T cell activity, we now provide a comprehensive analysis of the in vivo distribution of Foxp3+CD4+CD25+ cells in wild-type mice, and during cure of experimental colitis. In both cases, Foxp3+CD4+CD25+ cells were found to accumulate in the colon and secondary lymphoid organs. Importantly, Foxp3+ cells were present at increased density in colon samples from patients with ulcerative colitis or Crohn's disease, suggesting similarities in the behavior of murine and human regulatory cells under inflammatory conditions. Cure of murine colitis was dependent on the presence of IL-10, and IL-10-producing CD4+CD25+ T cells were enriched within the colon during cure of colitis and also under steady state conditions. Our data indicate that although CD4+CD25+ T cells expressing Foxp3 are present within both lymphoid organs and the colon, subsets of IL-10-producing CD4+CD25+ T cells are present mainly within the intestinal lamina propria suggesting compartmentalization of the regulatory T cell response at effector sites.